CORPORATE SOCIAL RESPONSIBILITY AND TAX AGGRESSIVENESS IN PERSPECTIVE LEGITIMACY THEORY - Putri Sari; Wiwiek Prihandini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The company as a business entity seeks to provide high dividends for shareholders. On the other hand as a corporate taxpayer, companies must set aside profits to pay taxes. Tax aggressiveness can be used to minimize this conflict. But this action is not liked by shareholders because it can damage the company's reputation. By referring to the legitimacy theory, corporate social responsibility (CSR) is considered as an action that can maintain the company's reputation. The question is whether corporate social responsibility has an effect on tax aggressiveness. In fact the results of the research on this matter vary. This study aims to reexamine the influence of corporate social responsibility, from the economic, social, and environmental dimensions to tax aggressiveness. The tests were carried out using 62 data from 31 companies listed on the Indonesia Stock Exchange during 2016-2017. Effective tax rate (ETR) is used to measure tax aggressiveness, CSR is measured using the Global Reporting Initiative (GRI) 04 valuation standard. The results of the study state that CSR economic dimension has a positive effect on tax aggressiveness, while CSR social and environmental dimensions negatively affect tax aggressiveness. Recommendations, tax authorities can use disclosure of environmental and social dimensions as an indication of the practice of tax aggressiveness. Key Words: Corporate Social Responsibility (CSR), Tax Aggressiveness, Legitimacy Theory, Global Reporting Initiative (GRI).